Maqāṣid Al-Syarī‘ah and Female Leadership in the Muslim Family: Towards an Integrative Conceptual Model - Anisa, Lina Nur (IAIN Manado, 2025)
This study aims to examine how women’s leadership roles in households can be conceptualized through the lens of maqāṣid al-syarī‘ah and modern sociology, offering an integrative framework that aligns normative Islamic principles with observed social dynamics. Using a library research approach, the study systematically analyzes authoritative Islamic legal sources, classical and contemporary sociological theories, and findings from existing empirical studies on family roles and gender relations. Rather than conducting original fieldwork, this research synthesizes prior empirical evidence to assess the normative legitimacy, functional dimensions, and societal implications of female leadership in the family. The analysis shows that the objectives of maqāṣid al-syarī‘ah—the protection of religion, life, intellect, progeny, and wealth—are compatible with sociological perspectives on gendered decision-making, role flexibility, and family well-being. This synthesis results in a conceptual model that supports equitable role distribution, promotes justice, and strengthens family resilience amid socio-cultural change. The study concludes that empowering women in family leadership roles, when grounded in both Islamic objectives and sociological insights, contributes to a more balanced and sustainable household structure, and it recommends future empirical research to test and contextualize this model across diverse cultural settings.